Congenital spinal tumor in a patient with encephalocele and hydrocephalus: a case report - Mahjoub Fatemeh; Nejat Farideh; Radmanesh Farid; El Khashab Mostafa (Journal of Medical Case Reports, 2011)
Abstract Introduction Encephalocele is a rare congenital abnormality of the central nervous system, where brain tissue protrudes from a defect in the skull. Some anomalies are associated with encephalocele. However, the association of spinal teratoma and encephalocele has not been reported in the English literature. Case presentation We report the case of an Iranian girl with a history of encephalocele surgery, who, at the age of four years, developed an intramedullary spinal teratoma, and discuss the pathogenesis of this association. Conclusion To the best of our knowledge, this is the first report of an association between encephalocele and spinal teratoma.